PNMA5 Promotes Bone Metastasis of Non-small-Cell Lung Cancer as a Target of BMP2 Signaling - Huang, Fei; Cao, Yaqiang; Wang, Caihong; Lan, Ruilong; Wu, Bing; Xie, Xianhe; Hong, Jinsheng; Fu, Lengxi; Wu, Gui (Frontiers in Cell and Developmental Biology, 2021)
Bone metastases frequently occur in NSCLC patients at the late stage, indicating poor survival. However, mechanisms about the initiation of NSCLC bone metastases remain largely unclear. In our previous reports, BMP2 signaling activation has been found to enhance NSCLC bone metastases through enhancing carcinoma cells migration, invasion, osteoclasts differentiation and osteoblasts immature differentiation. Nevertheless, downstream target genes of BMP2 contributing to those processes still remain unknown. In this project, we find that the expression of PNMA5 is higher in metastatic bone tumors of Lewis lung carcinoma than in metastatic lung tumors and parental Lewis lung cells. PNMA5 overexpression not only can promote cell migration and invasion of NSCLC cells but also tumor-induced osteoclasts differentiation. Interestingly, knockdown of Pnma5 in Lewis lung cells blocks BMP2 signaling from inducing Lewis lung cells migration and invasion. Although BMP2 signaling can promote Lewis lung cells-induced osteoclasts differentiation from macrophages, this effect can also be blocked when Pnma5 is knocked down in Lewis lung cells. Moreover, PNMA5 can promote NSCLC bone metastases in vivo as the downstream target of BMP2. Those results above indicate that BMP2 signaling enhances NSCLC bone metastases via its direct downstream target gene PNMA5.This research reveals the detailed molecular mechanism about how BMP2 signaling contributes to NSCLC bone metastases and provides a new potential therapeutic target for the treatment of NSCLC bone metastases.